L’ethnographe dans le sous-terrain : Fragments biographiques - Beauchez, Jérôme (Anthropologica, 2017)
This essay proposes to enter the underground of the ethnographer, in the sense of a breakthrough in the researcher’s biography striving to accomplish this gesture Georges Devereux recommended us as observers of human behavior: trying to understand ourselves in order to better understand what we transfer in the subjects-objects of our knowledge. The materials of this reflection consist of biographical fragments that reveal some foundational issues of a research career. Against any self-analytical illusion, fieldwork on the ground is therefore considered from the underground that founded it without considering that the latter could appear in all the clarity of conscience for which it still keeps its dark side.